Cycling infrastructures and equity: an examination of bike lanes and bike sharing system in Lisbon, Portugal - Padeiro, Miguel (2022)
Inequity of access to the cycling network may reinforce social disparities in health and access to resources and opportunities. This study aims to examine whether the area-level material deprivation index is associated with different levels of accessibility to Lisbon’s (i) cycling network and (ii) bike-sharing docking stations network. Independent t-tests were implemented, and regression models were performed to estimate the associations of the multiple deprivation index with each dependent bike lane and bike-sharing docking station variable, adjusting for covariates. The results confirm the hypothesis of a significant difference between the most and least deprived areas in terms of the presence of bike lanes and bike-sharing stations as well as in terms of coverage, distance, and connectivity of the both infrastructures. When covariates are controlled, a higher index of material deprivation is associated with (i) a lower presence of, greater distance to, and lower coverage of bike-sharing docking stations; and (ii) is not associated with the presence of, distance to, connectivity of, and coverage of cycle lane networks. Based on these findings, efforts should be directed to increase access to bike lanes and bike-sharing systems to more deprived areas.